Market efficiency or not: a study of emerging market of colombo stock exchange (cse) in sri lanka - Arulvel, K.K.; Balaputhiran, S.; Ramesh, S.; Nimalathasan, B. (University of Jaffna, 2011)
Efficient market is one in which prices fully reflect available information. An implication of an efficient market is that no excess returns can be made from this information because current prices already reflect the information. However, excess returns (if any) should not be statistically significant from zero. Market efficiency depends on the ability of traders to devote the time and resources to gather and disseminate information. The objective of the study is to find out the market efficiency of the CSE in Sri Lanka. ‘Event study’ methodology is applied to investigate Market efficiency. The results revealed that there is an evidence of an anticipatotary effect (CAARs = 5.67%) during the pre announcement period (-10,-1) because of information leakage and also large CAAR (5.76%) is observed during the period of (0, 10) due to investors do not adjust quickly to the information and a considerable amount of time passes before the prices fully incorporates relevant information in dividends.
Keywords: Market efficiency; Emerging market and event study